Post-pandemic self-reported mental health of mental healthcare professionals in the Netherlands compared to during the pandemic – an online longitudinal follow-up study - de Vroege, Lars; van den Broek, Anneloes (Frontiers in Public Health, 2023)
The mental health of professionals was under pressure during- and post-pandemic. Initially, the focus was mainly on the health workers in the hospitals, but over time the pressure shifted to other sectors, including mental health care. An increase in workload and decrease in mental health of healthcare professionals in mental health care can lead to a decrease in the available care capacity. In an earlier online survey of mental health professionals, 1300 professionals from a large number of mental healthcare institutions were involved. In this study, conducted in September 2021, about half of the respondents reported increased levels of stress. Feelings of anxiety, anger, and sadness were also increasingly experienced due to the COVID-19 pandemic. Furthermore, 4.2% replied that they were considering resigning their jobs. One of the recommendations of this previous study was to monitor these professionals repeatedly to be able to make an estimate of the stress and vision of work during the course of the pandemic and afterwards. Following this recommendation, the online survey was repeated. The aim of the current online longitudinal follow-up study was to re-evaluated mental status of healthcare workers. 510 healthcare workers participated in this follow-up survey. The reported mental health complaints were significantly higher during compared to post-pandemic. Respondents were less able to maintain work/life balance during the pandemic and even reported a shift to work. However, the majority of respondents indicated that they had restored this balance post-pandemic. Moreover, more sick leave was reported post-pandemic than during the pandemic and